(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article studies the use and frequency of abbreviations and acronyms in British and American English. It explores how these linguistic phenomena differ in terms of formation, usage, and sociolinguistic function. Based on corpus linguistics, cognitive linguistics, and pragmatics, this study also highlights how cultural, historical, and technological factors influence abbreviation trends in each variety. Examples from real-world contexts, such as media, business, and technology, demonstrate how American English often prioritizes brevity and innovation, whereas British English emphasizes institutional stability and traditional expressions. Findings underscore the importance of understanding these variations for linguists, translators, and ESL learners.